Hemodynamic Comparison of Treatment Strategies for Intracranial Vertebral Artery Fusiform Aneurysms - Jiang, Yeqing; Lu, Gang; Ge, Liang; Zou, Rong; Li, Gaohui; Wan, Hailin; Leng, Xiaochang; Xiang, Jianping; Zhang, Xiaolong (Frontiers in Neurology, 2022)
Objective This study comparatively analyzed the hemodynamic changes resulting from various simulated stent-assisted embolization treatments to explore an optimal treatment strategy for intracranial vertebral artery fusiform aneurysms. An actual vertebral fusiform aneurysm case treated by large coil post-stenting (PLCS) was used as a control. Materials and Methods A single case of an intracranial vertebral artery fusiform aneurysm underwent a preoperative and eight postoperative finite element treatment simulations: PLCS [single and dual Low-profile Visualized Intraluminal Support (LVIS)], Jailing technique (single and dual LVIS both simulated twice, Pipeline Embolization Device (PED) with or without large coils (LCs). Qualitative and quantitative assessments were performed to analyze the most common hemodynamic risk factors for recurrence. Results Jailing technique and PED-only had a high residual flow volume (RFV) and wall shear stress (WSS) on the large curvature of the blood flow impingement region. Quantitative analysis determined that PLSC and PED had a lower RFV compared to preoperative than did the jailing technique [PED+LC 2.46% < PLCS 1.2 (dual LVIS) 4.75% < PLCS 1.1 (single LVIS) 6.34% < PED 6.58% < Jailing 2.2 12.45% < Jailing 1.2 12.71% < Jailing 1.1 14.28% < Jailing 2.1 16.44%]. The sac-averaged flow velocity treated by PLCS, PED and PED+LC compared to preoperatively was significantly lower than the jailing technique [PED+LC = PLCS 1.2 (dual LVIS) 17.5% < PLCS 1.1 (single LVIS) = PED 27.5% < Jailing 1.2 = Jailing 2.2 32.5% < Jailing 1.1 37.5% < Jailing 2.1 40%]. The sac-averaged WSS for the PLCS 1.2 (dual LVIS) model was lower than the PED+LC, while the high WSS area of the Jailing 1 model was larger than for Jailing 2 [PLCS 1.2 38.94% (dual LVIS) < PED+LC 41% < PLCS 1.1 43.36% (single LVIS) < PED 45.23% < Jailing 2.1 47.49% < Jailing 2.2 47.79% < Jailing 1.1 48.97% < Jailing 1.2 49.85%]. Conclusions For fusiform aneurysms, post large coil stenting can provide a uniform coil configuration potentially reducing the hemodynamic risk factors of recurrence. Flow diverters also may reduce the recurrence risk, with long-term follow-up required, especially to monitor branch blood flow to prevent postoperative ischemia.